2003
DOI: 10.1046/j.1365-2427.2003.01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of the flora and macroinvertebrate fauna of a chalk stream site to changes in management

Abstract: SUMMARY 1. Temporal changes in a series of habitats and their macroinvertebrate assemblages were examined on a 50‐m section of a chalk stream in Berkshire, England between June 1975–79 and June 1997–2001. 2. The site was part of a trout fishery in 1975–79, when river management included instream weed cutting together with control of bankside trees and riparian vegetation. Management ceased in the 1980s and by 1997–2001, the site was heavily shaded by trees and riparian vegetation. 3. The mean area of instream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
(41 reference statements)
2
21
0
Order By: Relevance
“…As expected, the Lambourn at Bagnor differed from the three Kennet sites, not only because it was on a tributary of the Kennet but also due to the heavy shading (Wright et al, 2003). Ephemerellidae, Baetidae and frequently Chironomidae were less abundant at Bagnor, whereas Glossosomatidae occurred at higher densities.…”
Section: Changes In Faunal Assemblages At Each Site and Habitat Betwesupporting
confidence: 59%
See 1 more Smart Citation
“…As expected, the Lambourn at Bagnor differed from the three Kennet sites, not only because it was on a tributary of the Kennet but also due to the heavy shading (Wright et al, 2003). Ephemerellidae, Baetidae and frequently Chironomidae were less abundant at Bagnor, whereas Glossosomatidae occurred at higher densities.…”
Section: Changes In Faunal Assemblages At Each Site and Habitat Betwesupporting
confidence: 59%
“…Some of the major differences (see Appendix) included higher densities of Baetidae and Ephemerellidae on the three unshaded Kennet sites than on the equivalent habitat at the heavily shaded Bagnor site. However, shading does appear to favour Glossosomatidae at Bagnor (Wright et al, 2003). A number of families including Simuliidae and Chironomidae, in addition to Baetidae and Ephemerellidae, generally occurred at higher densities on macrophytes compared to gravel, irrespective of site.…”
Section: Resultsmentioning
confidence: 92%
“…Previous investigations demonstrated that the spatial distribution of macrophytes in lowland stream reaches changes in response to physical degradation or impact (Baattrup-Pedersen et al, 2002;Wright et al, 2003). The STAR sampling methodology (MTR & RHS) does not allow distribution changes within reaches to be examined.…”
Section: Pca1mentioning
confidence: 99%
“…Conversely, excessive macrophyte growth in lowland catchments, particularly within unshaded reaches and those affected by agricultural runoff and sewage effluent, can represent a significant flood risk and exceed optimum levels of plant growth for river biota (Haslam, 1978;Wright et al, 2003). Different plant morphologies have different impacts on the flow environment (Naden et al, 2006), but overall aquatic macrophytes are observed to increase hydraulic roughness, modify velocity patterns and promote deposition of fine sediments (Gregg and Rose, 1982;Gurnell et al, 2006;Wharton et al, 2006).…”
Section: Introductionmentioning
confidence: 99%